Følelser ved fronten – og i eftertiden - Petersen, Kamilla Ane (Fra Krig og Fred, 2026)
During the Great Patriotic War, which was the war between the Krasnaya Armiya (Stalins’s Red Army) and the Ostheer (Hitler’s army at the eastern front) in 1941-1945, approximately 800.000 women joined the Red Army. This study examines the participating women’s emotionally laden stories, as they are presented in the monograph The Unwomanly Face of War by author and journalist Svetlana Alexievich. Ever since the publication of Alexievich’s monography historians have used these oral stories when trying to explain women’s motivation to join the Red Army to fight against the German enemy. However, few have combined oral history and history of emotions in a way to investigate these women’s stories. By focusing on three emotional terms; shame, fear and happiness this study shows that the women’s emotionally laden stories reveal sensitive but above all gender related themes. Furthermore, women’s emotionally laden stories are a window through which we see how women in the late 70’s Soviet Union tries to dissociate themselves from the grand narrative and society’s view on women in war.